'Aisyiyah's Legal Aid Model in Medan City - Fajaruddin Fajaruddin; Rasta Kurniawati Pinem (International Journal Reglement & Society (IJRS), 2020)
'Aisyiyah, as one of the women's movements that has a concern for the empowerment and development of community law, feels the need to be involved in supporting increased public access to justice and legal certainty. The method used in this research is empirical legal research which combines the data obtained from library materials with data obtained from the field and then analyzed qualitatively. From the research results, it is known that the Regional Leadership of 'Aisyiyah Medan City has a special model in providing legal assistance to women in Medan City, in the form of counseling at the' Aisyiyah recitation place with more material on the defense and protection of the rights of women and children. Legal aid that is carried out tends to be non-litigation. This is in accordance with the character of the da'wah of 'Aisyiyah / Muhammadiyah, it is better to prevent than to treat it, to anticipate is better than to go to court, to make peace is better than face to face in court, because Islam teaches peace and brotherhood. If any of your brothers are at odds then reconcile the two.